1998
DOI: 10.5271/sjweh.369
|View full text |Cite
|
Sign up to set email alerts
|

Work-related low-back problems in nursing

Abstract: This scientific literature review focuses 011 the relation bctween nursing work and low-back problems. Its ail11 was to estimate thc risk of physical, psychosocial, and work organizational exposure factors that may lead to low-back problems. In addition this paper reviews and evaluates reported ergonomic intervention, with thc object of decreasing the prcvalcnce and incidence of low-back problems among nurses. A co~isiderable numbcr of studies of ~iursing staff has shown thc connection between lifts and transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
100
1
4

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(111 citation statements)
references
References 62 publications
6
100
1
4
Order By: Relevance
“…It has also been pointed out that care by the caregiver should be performed with the right posture to reduce the burden on their own lower back [30,31]. Environmental maintenance and the placement of enough staff are ideals for the prevention of low back pain in nursing home caregivers [32], but the universal application of such concepts cannot occur in nursing homes in Japan because the reward is limited by the nursing care insurance. When caregivers assume a concept of ''protecting one's body by oneself'', comprehensive staff education on features such as the right posture for care, preventive exercise, and wearing a belt is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been pointed out that care by the caregiver should be performed with the right posture to reduce the burden on their own lower back [30,31]. Environmental maintenance and the placement of enough staff are ideals for the prevention of low back pain in nursing home caregivers [32], but the universal application of such concepts cannot occur in nursing homes in Japan because the reward is limited by the nursing care insurance. When caregivers assume a concept of ''protecting one's body by oneself'', comprehensive staff education on features such as the right posture for care, preventive exercise, and wearing a belt is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews (Lagerstrom et al, 1998, Menzel, 2004, Sherehiy et al, 2004 have shown that qualification level and therewith associated different exposure and tasks are associated with the risk for spine complaints. Consequently, the distinction between nurses and auxiliary staff was used as separate risk factor, with registered nurses as the reference category.…”
Section: Individual Factorsmentioning
confidence: 99%
“…Pesquisadores de várias partes do mundo têm demonstrado que os trabalhadores de enfermagem são um dos grupos ocupacionais mais afetados por algias e lesões dorsais ocupacionais (1)(2)(3)(4) . Países desenvolvidos têm voltado sua atenção especificamente aos acidentes do trabalho que comprometem a coluna e já foi comprovado que a equipe de enfermagem apresenta uma das maiores taxas de ocorrência deste tipo de acidente (5)(6)(7)(8)(9)(10) .…”
Section: Introductionunclassified